Making energy metrics relevant to service firms: from energy conservation to energy productivity. (20th May 2020) - Raggio, Randle D.; Ekman, Peter; Thompson, Steven M.
Abstract: Although energy conservation and reduction in environmental impact are on the international and most national agendas, service firms rarely include energy consumption metrics in their strategic decision-making. One reason for the omission is that for service industries, firm level energy utilization is most commonly measured in kilowatt hours per square meter of office space where changes often related to the space rather than the firm performance. The measure also presents several problems for firms in service industries. First, energy conservation and reduction may be counterproductive for service firms that are growing and require energy to sustain that growth. Second, it may not relate to national and international goals which are often focused on the amount of carbon dioxide produced generating energy than the total amount of energy consumed. Third, it treats energy as a utility rather than a resource in firms' value creation. Results from a field study focused on service firms in Sweden suggests that focusing on energy productivity overcomes the limitations of existing measures and produces positive results. By conceptualizing energy productivity as output per unit of energy, we create a conservation metric that enables service firms to measure their contributions to energy consumption relative to national economic growth. As a result, energy productivity aligns the interests of service organizations with those of policy makers and conservationists. Highlights: Describes how energy use can become an integrated part in the management of service firms. Measures energy utilization per square meter of space and per employee, do not reliably capture changes in sustainable efforts. Energy consumption relative to value creation is a better measure for stimulating energy efficiency within service firms. Energy productivity metric for service firms relates energy usage to organizational and national sustainability goals